1996
DOI: 10.1177/00220345960750030401
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Transmission Electron Microscopy Examination of Nondemineralized and Demineralized Resin-Dentin Interfaces Formed by Two Dentin Adhesive Systems

Abstract: The resin-dentin interface formed by two dentin adhesives, Optibond (OPTI, Kerr) and Scotchbond Multi-Purpose (SBMP, 3M), was ultramorphologically examined by transmission electron microscopy (TEM). Ultrastructural information from nondemineralized and demineralized sections was correlated. It was hypothesized that the different chemical formulations of the two adhesives would result in a different morphological appearance of the hybrid layer. Ultrastructural TEM examination proved that each of the two dentin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 16 publications
8
87
1
1
Order By: Relevance
“…It should be taken into account that the clinical significance of the high microleakage scores obtained with the use of polyalkenoic acid-based adhesives (e.g., SBMP) is controversial; 25 their clinical retention rate at 3 years is unexpectedly high, which may be related to theirs stressrelaxation capacity. 25,30 On gingival margins, none of the restorative systems under study completely resisted microleakage, consistent with the findings of other studies. 4,31 CSEB showed lower dye penetration values compared with E&P, as reported by other authors.…”
Section: Discussionsupporting
confidence: 87%
“…It should be taken into account that the clinical significance of the high microleakage scores obtained with the use of polyalkenoic acid-based adhesives (e.g., SBMP) is controversial; 25 their clinical retention rate at 3 years is unexpectedly high, which may be related to theirs stressrelaxation capacity. 25,30 On gingival margins, none of the restorative systems under study completely resisted microleakage, consistent with the findings of other studies. 4,31 CSEB showed lower dye penetration values compared with E&P, as reported by other authors.…”
Section: Discussionsupporting
confidence: 87%
“…The possible explanation for this finding may be related to the mixture among the primer and adhesive resin components within the hybrid layer when Pre-Bond is applied to the primed surface. Composed of a high concentration of hydrophobic monomers, such as Bis-GMA (Table 1), Pre-Bond adhesive resin may create a hybrid layer with a high concentration of hydrophobic monomers and, consequently, lower hydrophilicity, [14][15][16] thus improving its mechanical properties. [17][18] Moreover, dual-curing mechanisms within the hybrid layer may have contributed to the higher µTBS when Pre-Bond resin infiltrated the primed dentin surface.…”
Section: Fractured Specimen Using All Bond 2 When Primer Was Light mentioning
confidence: 99%
“…This high variance indicated the unpredictability of the demineralization process in carious lesions. Van Meerbeek et al [11] demonstrated that, in some dentin bonding systems, there was a discrepancy between the depth of dentin demineralization and the depth of resin infiltration. In our investigation, this discrepancy was more obvious in the pink zone bonded with the etch-rinse system.…”
Section: Discussionmentioning
confidence: 99%
“…A bond between adhesive resin and dentin depends on the penetration of the primer and adhesive resin into the conditioned dentin surface to create micromechanical interlocking between the dentin collagen and resin, forming a hybrid layer [10]. The formation of the hybrid layer may be affected by chemical composition and application mode of adhesive systems [11], differences in the dentin location [12,13] and changes in the microstructural features of dentin associated with the caries process [14]. Several previous studies have shown that the hybrid layer created by etch-rinse systems is significantly thicker than that created by self-etch primers [14][15][16] since they are more acidic and therefore result in a deeper demineralized layer.…”
Section: Introductionmentioning
confidence: 99%